2012
DOI: 10.1111/j.1468-1331.2012.03771.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a weight loss program on migraine in obese adolescents

Abstract: Significant improvements in both adiposity and headache data were observed in obese adolescents with migraine who participated in a 12-month-long interdisciplinary intervention program for weight loss. Initial body weight and amount of weight loss may be useful for clinicians to predict migraine outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 10 publications
(17 reference statements)
3
81
0
4
Order By: Relevance
“…Comorbidity with obesity has been reported in children and in adults with headaches (3,(23)(24)(25), but both of these conditions are widespread and conclusive results are difficult to obtain. In obese …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comorbidity with obesity has been reported in children and in adults with headaches (3,(23)(24)(25), but both of these conditions are widespread and conclusive results are difficult to obtain. In obese …”
Section: Discussionmentioning
confidence: 99%
“…Other associated conditions are epilepsy (10-15), asthma and allergic disorders (16), sleep disorders (17-21), celiac disease (CD) (22), and obesity (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BKİ azaltmanın migreni hafifletip hafifletmeyeceği değerlen-dirmek için, 135 ergende diyet, sistemik egzersiz ve davranışsal terapi içeren kütle azaltma programı uygulamıştır. 22 Projeden 12 ay sonra, çalışma yürütü-cüleri kilo, BKİ, bel çevresi ile migren ataklarının yoğunluğu, sıklığı ve ilaç alımının ihtiyacı konusunda istatiksel olarak bir düşüş elde etmişlerdir. Soruna yönelik bu yaklaşım BKİ ve baş ağrılarının sıklığı arasındaki ilişkiye ışık tutmaktadır.…”
Section: Beden Kütle İndeksi̇ (Bki̇) Ve Mi̇grenunclassified
“…Particularly in patients suffer from morbid obesity that has higher frequency of migraine headache. Recently, it has been showed that surgical weight loss with bariatric surgery can improve migraine headache in morbidly obese patients (19,20).…”
Section: Introductionmentioning
confidence: 99%